(untitled) (Journal of Information Technologies in Education (ITE), 2015)
One of the main factors of successful employment is a choosing a profession, which would be demanded enough at the modern labour market. According to the opinion of many experts, development of modern technologies is the main factor that stimulates growth of productivity and economy in general. This trend is characterized by the state of a labour market, when a significant amount of perspective professions is connected to IT field, which is a worldwide trend. Actually, a job of a programmer has become one of the most demanded specialties on a labour market. As for today, web development is a mainstream in software development. This article describes the requirements for web developers, requirements to the frontend and backend developers. We consider skill levels and requirements. Considered programming languages to learn. These are HTML5, XML, ccs3, javascript+, PHP, sql. Considered particular certification level programmers. The content of the discipline "Web development" is alighted to obtain the necessary skills and knowledge in this area. It also considers the structure of a basic study guide of the discipline.